HUBUNGAN ANTARA PERBEDAAN PERMANEN DAN PERBEDAAN WAKTU DENGAN PERSISTENSI LABA - Sheila Ajrina; Santi Susanti; Achmad Fauzi (Faculty of Economics, State University of Jakarta., 2014)
The purpose of this research is to examine the correlation of permanent differences and timing differences with earning persistence at manufacturing companies listed in Indonesia Stock Exchange in 2013. This research used the survey method with correlational approach using secondary data which was obtained from manufacturing companies listed in Indonesian Stock Exchange. The results of this research indicate that (i) permanent differences and timing differences simultaneously had a significant correlation with earning persistence, (ii) permanent differences had a negative significant correlation with earning persistence and, (iii) timing differences had a negative significant correlation with earning persistence. The conclusion of the research is information in timing and permanent differences had opposite direction of correlation with earning persistence, which is when timing and permanent differences partially increased, the earning persistence will be decreased and timing and permanent differences simultaneously had enough rate of correlation with earning persistence. Keywords: Permanent Differences, Timing Differences, Earning Persistence.